INTEGRATION OF SHARIA NORMS IN THE FORMATION OF REGIONAL REGULATIONS IN INDONESIA: JURIDICAL ANALYSIS OF THE FORMATION OF SHARIA REGIONAL REGULATIONS - Ahmad Lutfi Rijalul Fikri; Hermawati Hermawati (STIS Darussalam Bermi, 2024)
This study examines the latest practices of integrating Sharia norms in the formation of Regional Regulations (Perda) in Indonesia and performs a jurisprudential analysis of such practices. The study found that there are at least 442 Sharia-nuanced Perdas that have been established in various parts of Indonesia, such as the provinces of Aceh, Western Sumatra, Banten, and South Sulawesi. The Perda regulates various aspects, such as the implementation of Islamic Shariah, the prohibition of prostitution, the application of compulsory reading of the Qur'an, and the arrangement for Islamic clothing. Juridical-normative analysis suggests that the practice of integrating Sharia norms into the establishment of the Perda must be in accordance with the principles contained in the 1945 Basic Law, in particular concerning guarantees of religious freedom and prohibition of discrimination. Such regulations must also be in line with the hierarchy of laws in force in Indonesia, not in conflict with higher regulations. The Charter of Sharia must guarantee the protection of human rights, such as religious freedom, freedom of opinion, and other constitutional rights. The process of forming the Shariah Perda needs to involve widespread public participation in order to acquire strong legitimacy. Furthermore, a comprehensive evaluation of the charges, purposes and processes of the establishment of the Sharia law is required to ensure its compatibility with the principles of a democratic rule of law.